First person - Tuba Sural-Fehr (The Company of Biologists, 2019)
First Person is a series of interviews with the first authors of a selection of papers published in Disease Models & Mechanisms (DMM), helping early-career researchers promote themselves alongside their papers. Tuba Sural-Fehr is first author on 'Inhibition of the IGF-1-PI3K-Akt-mTORC2 pathway in lipid rafts increases neuronal vulnerability in a genetic lysosomal glycosphingolipidosis', published in DMM. Tuba conducted the research described in this article while a Postdoctoral Fellow in Dr Ernesto Bongarzone's lab at University of Illinois-Chicago, Chicago, USA.